Hybrid coronary revascularization for the treatment of multivessel coronary artery disease - Kayatta, Michael O.; Halkos, Michael E.; Puskas, John D. (Annals of Cardiothoracic Surgery, 2018)
Coronary artery disease (CAD) has typically been treated either medically, with percutaneous coronary intervention (PCI), or with coronary artery bypass grafting (CABG). As advances in stent technology and minimally invasive surgery have developed, a third option has emerged: hybrid coronary revascularization (HCR). In HCR, minimally invasive CABG and PCI are both employed to treat a single patient, often during the same hospital stay. Patients appropriate for this technique vary widely, from low-risk patients with low SYNTAX lesions outside the left anterior descending artery (LAD), to high-risk patients with multiple comorbidities who are felt by the heart team to benefit most by avoiding a sternotomy. Across both our experience and other series in the literature, mortality with HCR is around 1%. Hospital length of stay is less than one week, and typically less than after conventional CABG, but longer than with isolated PCI. Return to baseline activity is substantially shorter after minimally invasive CABG compared to conventional CABG due to the avoidance of a sternotomy; deep sternal wound infections are entirely avoided. Mid-term need for repeat revascularization may be higher with HCR, though randomized data are lacking. In conclusion, HCR is an evolving method to treat multivessel CAD with favorable early results in high volume centers, though growth in the field is limited by surgical experience and success with minimally invasive techniques.